The fungal colony : symposium of the British Mycological Society held at the Scientific Societies Lecture Theatre, in London, September 1997 - British Mycological Society. Symposium (1997 : London, England); Gow, Neil A. R.; Robson, G. D. (Geoffrey D.); Gadd, Geoffrey M. (Cambridge : Cambridge University Press, 1999)
42